2021
DOI: 10.1177/1971400921990770
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial ependymomas: The role of advanced neuroimaging in diagnosis and management

Abstract: Intracranial ependymomas represent a rare subgroup of glial tumours, showing a wide variety of imaging characteristics, often representing a challenging diagnosis for neuroradiologists. Here, we review the most recent scientific Literature on intracranial ependymomas, highlighting the most characteristic computed tomography and magnetic resonance imaging features of these neoplasms, along with epidemiologic data, recent classification aspects, clinical presentation and conventional therapeutic strategies. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…In the ST group, studies have shown that YAP1 fusions foretell an excellent prognosis, with 5-year PFS and OS of 66 and 100%, respectively, whereas the presence of RELA fusions, which occurs in more than 70% of cases, correlates with some of the poorest outcomes (5 years PFS and OS of 29 and 75%, respectively) 4 . Despite this, these differences have not yet been translated into significant differences in the therapeutic management of these injuries 9 . Unfortunately, in the reported case, RELA fusion was not researched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ST group, studies have shown that YAP1 fusions foretell an excellent prognosis, with 5-year PFS and OS of 66 and 100%, respectively, whereas the presence of RELA fusions, which occurs in more than 70% of cases, correlates with some of the poorest outcomes (5 years PFS and OS of 29 and 75%, respectively) 4 . Despite this, these differences have not yet been translated into significant differences in the therapeutic management of these injuries 9 . Unfortunately, in the reported case, RELA fusion was not researched.…”
Section: Discussionmentioning
confidence: 99%
“…The most common are surface scanning, photogrammetry, computer tomography (CT) or magnetic resonance imaging (MRI) reconstruction, and digital modeling 7 . 3D models of anatomical structures are arising as important tools for surgery planning and medicine teaching [7][8][9] . This article, written following CARE guidelines, addresses the case of a 3-year-old female patient with recurrent supratentorial ependymoma and presents a unique 3D reconstruction model of the intracranial lesion, in order to discuss the surgical approach and the new possibilities offered by these technologies.…”
Section: Introductionmentioning
confidence: 99%